Investigating the Role of Hard Skill and Soft Skill on Teacher Innovations : PLS-SEM Analysis - Asbari, Masduki (AGUSPATI RESEARCH INSTITUTA, 2024)
This research aims to measure the influence of hard skills and soft skills on teachers' innovation abilities in Banten which are mediated by organizational learning. Data collection was carried out by simple random sampling via electronics to the teacher population in Banten The results of the questionnaire that were returned and valid were 897 samples. Data processing uses the SEM method with SmartPLS 3.0 software. The results of this research conclude that hard skills and soft skills have a positive and significant effect on teachers' innovation abilities, both directly and indirectly through the mediation of organizational learning. This new research proposes a model for building teacher innovation capabilities among teachers through improving hard skills and soft skills with organizational learning as a mediator. This research can pave the way for increasing teacher readiness in facing the education era 4.0.